THE SPEAKING ACTIVITY SAMPLES IN EFL TEXTBOOKS - Mavlanova, Dildora (Журнал иностранных языков и лингвистики, 2023)
In general, the present study aims to investigate different aspects of foreign language education covering the significance of the CEFR as a language policy model for practitioners and the kind of discourse promoted in EFL course books.